SmMYB2 promotes salvianolic acid biosynthesis in the medicinal herb Salvia miltiorrhiza. Issue 11 (3rd June 2020) - Deng, Changping; Wang, Yao; Huang, Fenfen; Lu, Sunjie; Zhao, Limei; Ma, Xingyuan; Kai, Guoyin
Abstract: MYB transcription factors play vital roles in plant growth and metabolism. The phytohormone methyl jasmonate (MeJA) promotes phenolic acid accumulation in the medicinal herb Salvia miltiorrhiza, but the regulatory mechanism is poorly understood. Here, we identified the MeJA‐responsive R2R3‐MYB transcription factor gene SmMYB2 from a transcriptome library produced from MeJA‐treated S. miltiorrhiza hairy roots. SmMYB2 expression was tightly correlated with the expression of key salvianolic acid biosynthetic genes including CYP98A14 . SmMYB2 was highly expressed in the periderm of S. miltiorrhiza and SmMYB2 localized to the nucleus. Overexpressing SmMYB2 in S. miltiorrhiza hairy roots significantly increased the levels of salvianolic acids (including rosmarinic acid and salvianolic acid B) by upregulating salvianolic acid biosynthetic genes such as CYP98A14 . SmMYB2 binds to the MYB‐binding motifs in the promoter of CYP98A14, as confirmed by a dual‐luciferase assay and electrophoretic mobility shift assays. Anthocyanin contents were significantly higher in SmMYB2‐ overexpressing hairy root lines than the control, primarily due to the increased expression of CHI, DFR, and ANS . These findings reveal the novel regulatory role of SmMYB2 in MeJA‐mediated phenolic acid biosynthesis, providing a useful target gene for metabolic engineering and shedding light on the salvianolic acid regulatory network. Abstract : This work uncovered a novel MeJA‐responsive R2R3‐MYB transcription factor SmMYB2 that promotes salvianolic acid biosynthesis through activating the biosynthetic gene CYP98A14 as well as increases anthocyanin accumulation by upregulating the pathway gene CHI, DFR, and ANS in an important medicinal plant Salvia miltiorrhiza .